Color and aroma changes in potato and chicken meat due to maillard reaction during roasting - Jaclyn Regina Anggara; Sharon Gisella Tambayong; Elbert Keene Wibowo; Fransisca Romana Titis Suniati (Bahasa Indonesia, 2026)
The Maillard reaction is a non-enzymatic browning process that occurs between reducing sugars and amino acids during heating, playing a key role in the development of color and aroma in food products. This study aims to evaluate the changes in color and aroma resulting from the Maillard reaction in food products subjected to different heating durations. Objective color analysis was performed using a colorimeter to measure browning index (BI), chroma, and °hue, as well as spectrophotometric analysis, while aroma was assessed subjectively. The results indicated that heating duration significantly influenced color changes and melanoidin formation in chicken, as evidenced by increased BI and chroma values, along with shifts in °hue. In contrast, although absorbance increased in potato samples, the color change was not significant, likely due to the low levels of reducing sugars, fat, and protein. Heating also enhanced the characteristic aroma of both chicken and potatoes, attributed to the formation of volatile compounds through the Maillard reaction.